Detection of Neisseria gonorrhoeae or Chlamydia trachomatis from oral wash specimens using the Abbott RealTime CT/NG assay and the Cobas 4800 CT/NG assay: A prospective study. Issue 4 (April 2022) - Matsumoto, Masahiro; Hamasuna, Ryoichi; Le, Phuong Thi; Fujimoto, Naohiro; Matsumoto, Tetsuro
Abstract: Introduction: Isolating oropharyngeal Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) from oral wash specimens (OWSs) is uncommon. Therefore, we evaluated the performance of the Abbott RealTime CT/NG assay and the Cobas 4800 CT/NG assay in detecting NG and CT in OWSs. Methods: This multicenter prospective study included 457 patients from 14 medical facilities suspected of having untreated male urethritis or female cervicitis from November 2014 to December 2015. OWSs were collected and tested using the Abbott and Cobas assays. Finally, the discordant results were confirmed using the APTIMA Combo 2 transcription-mediated amplification assay and retested using each assay. Results: The sensitivity and specificity of the Abbott assay were 100% and 97.2% for NG and 87.5% and 100% for CT, respectively, and of the Cobas assay were 100% and 98.8% for NG and 93.8% and 99.8% for CT, respectively. Both assays had high negative but low positive predictive values for oropharyngeal NG (Abbott assay: 65.7%, Cobas assay: 82.1%). Based on the definition of "true positive, " the prevalence of oropharyngeal NG and CT were 5.0% and 3.5%, respectively. Conclusions: The Abbott and Cobas assays using OWSs had high sensitivity and specificity, which can help diagnose oropharyngeal NG and CT. We consider that if a positive result is obtained, the patient should be treated because the negative predictive values were high. However, limited data are available on oropharyngeal NG and CT detection, and further studies are needed to clarify the role of oropharyngeal sexually transmitted infections.